Botanics targets and therapy. ([Auckland, NZ] : Dove Medical Press, 2011)
"An international, peer-reviewed, open access journal focusing on the discovery and development of active compounds based upon or found naturally occurring in the plant kingdom that may have therapeutic potential in any disease state."
Articles added as received to annual volume in progress.
Articles in PDF and HTML format.
System requirements: Adobe acrobat reader.
Vol. 1 (2011); title from PDF caption (publisher's Web site, viewed Jan. 3, 2012).
Vol. 1 (2011) (viewed Jan. 3, 2012).
Keywords: Botany -- Periodicals; Botany, Medical -- Periodicals; Plants -- Therapeutic use -- Periodicals; Herbs & Medicinal Plants; Botany; Botany, Medical; Plants -- Therapeutic use; Herbal Medicine; Phytotherapy; Plants, Medicinal; Electronic journals